Evaluasi Kualitas Layanan Jaringan Wireless Di Jurusan Teknik Informatika Dan Komputer Fakultas Teknik Universitas Negeri Makassar - Sri Nurmulyani; Satria Gunawan Zain; Fathahillah Fathahillah (Jurnal Media Infotama, 2026)
This study aims to evaluate the quality of wireless network services in the Informatics and Computer Engineering Department, Makassar State University and analyze the evaluation results based on Quality of Service (QoS) parameters with reference to the TIPHON standard. This study uses an action research method with a repetitive cycle. Data were collected through direct measurements of QoS parameters such as throughput, packet loss, delay, and jitter at various access points in the department building. 2. Based on the data obtained, the average signal strength value (-65) with the category "fairly good", the average download speed value (13.48) with the category "fast/fairly good" and the average upload speed (9.27) with the category "moderate/good". Then the average value of QoS parameters after comparing the parameter index value with the TIPHON standard, the results of the study showed that the average value of the throughput index (3.6) is in the "very good" category, the average value of the packet loss index (3.3) is in the "good" category, the average value of the delay index (2.4) is in the "good" category, and the average value of the jitter index (3) is in the "good" category. After comparing the parameter index value with the TIPHON standard and performing normalization, the average value of the QoS index was (0.5625). This value shows that overall, the quality of wireless network services in the Informatics and Computer Engineering Department building is at a "fairly good" level.